Assessing community health workers’ level of knowledge concerning their roles in water, hygiene, and sanitation in Comè-Bopa-Grand Popo-Houéyogbé, Benin (2024) - Wouékpé, Parfait; Dégbey, Cyriaque; Kpozéhouen, Alphonse (Frontiers in Public Health, 2025)
ObjectivesThis study assessed the level of knowledge of community health workers (CHWs) regarding water, hygiene, and sanitation (WASH) in the Comè-Bopa-Grand Popo-Houéyogbé health zone in Benin.MethodsA cross-sectional survey was conducted among 160 CHWs selected randomly. Data were collected using a structured questionnaire and analyzed with SPSS 21.0. Logistic regression was used to identify factors associated with CHW knowledge.ResultsMost CHWs (68.8%) had insufficient knowledge of their roles in WASH. Factors significantly associated with good knowledge included Mina ethnicity (OR = 0.3; 95% CI: 0.1–0.9), being married (OR = 10.0; 95% CI: 1.3–77.7), training on activity packages (OR = 3.3; 95% CI: 1.7–10.0), supervision by a qualified agent (OR = 10.2; 95% CI: 2.5–40.6), and participation in group follow-up sessions (OR = 10.0; 95% CI: 5.0–48.9). Multivariate analysis showed that attending at least two group sessions greatly increased the likelihood of good knowledge (OR = 23.9; 95% CI: 5.3–107.7).ConclusionStrengthening CHW training, regular follow-up, and incentives is essential to improve WASH-related knowledge and public health impact.